THE BENEFITS OF SOFTWARE SOLUTIONS IN MEDICAL PATIENT CARE. A DOCVISER ONCOLOGY CASE STUDY. - Cristian BRICICARU; Ioana BELEIU (Annals of the University of Oradea: Economic Science)
This paper presents a study that looked at the influence of Docviser, an oncology patient management app, on the efficiency and quality of patient care in a hospital context. The research topic was whether doctors could take advantage of Docviser to save time on drug management activities and enhance dosage calculation accuracy. A semi-structured interview with a doctor who had been using Docviser for over a year was conducted. The software considerably reduced the time spent on medication management activities, with treatment administration time cut by at least two hours per patient, according to the data. According to the study, using Docviser provides evident benefits for patient care, such as greater speed and accuracy, as well as improved communication among doctors, pharmacists, and nurses. The findings have significance for medical practitioners, hospital administrators, and governments interested in improving patient care and lowering costs. The study's shortcomings include a small sample size and a narrow area of inquiry, indicating the need for additional research on the app's impact on costs as well as patient outcomes.